2022
DOI: 10.3390/jcm11195733
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance during Pregnancy and Influencing Factors in South Korea

Abstract: Pregnant women were excluded from vaccination against Coronavirus 2019 (COVID-19) until September 2021 in South Korea. Although vaccination for pregnant women started in October 2021, vaccine acceptance in pregnant women is yet unknown. This cross-sectional study aimed to investigate COVID-19 vaccine acceptance during pregnancy and influencing factors. An anonymous survey was distributed in obstetrics departments to all pregnant or postpartum women, during the prenatal or postpartum visit. The proportion of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These findings align with studies conducted in various countries, including the USA, China, France, the UK, Czechia, Switzerland, Turkey, India, South Korea, and Malaysia. [13][14][15][16][17][18][19][20][21]24 Notably, our study found that medical health provider recommendations were a significant factor that could nearly double the COVID-19 vaccine acceptance rate. This is consistent with the broader population in Thailand, where information from healthcare professionals is considered the most trustworthy source.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…These findings align with studies conducted in various countries, including the USA, China, France, the UK, Czechia, Switzerland, Turkey, India, South Korea, and Malaysia. [13][14][15][16][17][18][19][20][21]24 Notably, our study found that medical health provider recommendations were a significant factor that could nearly double the COVID-19 vaccine acceptance rate. This is consistent with the broader population in Thailand, where information from healthcare professionals is considered the most trustworthy source.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, countries like the UK (62.1%), Czechia (76.6%), India (78.52%), China (77.4%), and Malaysia (77.1%) demonstrate higher rates of willingness to receive the COVID-19 vaccine. [13][14][15][16][17][18][19][20][21]24 The predominant reason for vaccine hesitancy among Thai pregnant women was the fear that the vaccine might harm their babies, which likely contributed to the lower vaccine acceptance rate observed in our study. Interestingly, a different study conducted in Thailand reported a higher acceptance rate of 60.8%, 25 highlighting the contrasting results within the same country.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, a cross-sectional survey of US pregnant women showed that respondents who were recommended for COVID-19 vaccination by their healthcare provider were 52% more likely to accept the vaccine, reporting fewer concerns about vaccine safety and greater confidence in its effectiveness, compared to respondents with no provider recommendation [17]. Similarly, a Korean study demonstrated that patient education about maternal COVID-19 vaccination on the behalf of obstetrics and gynecology doctors is pivotal in increasing vaccination coverage [39]. Furthermore, a report from the CDC found that healthcare provider recommendations were associated with a higher likelihood of COVID-19 vaccination (77.6% vs. 61.9% of adults who did not receive a recommendation) [40].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, real-world evidence can help understand vaccine effectiveness against different disease severities in different susceptible populations often excluded from clinical trials [7], inform policy makers about the length of vaccine protection over time [8], and document rarer side effects [9]. Real-world data can also help understand the evolving prevalence and underlying causes of vaccine hesitancy over time [10] and shape future vaccination campaigns [11,12]. Understanding the role of herd immunity and how to promote vaccination are important questions that need reliable vaccination data [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%